LINC00518: a key player in tumor progression and clinical outcomes - Yi, Qiang; Zhu, Gangfeng; Zhu, Weijian; Wang, Jiaqi; Ouyang, Xinting; Yang, Kuan; Zhong, Jinghua (Frontiers in Immunology, 2024)
Long non-coding RNAs (lncRNAs), defined as RNA molecules exceeding 200 nucleotides in length, have been implicated in the regulation of various biological processes and the progression of tumors. Among them, LINC00518, a recently identified lncRNA encoded by a gene located on chromosome 6p24.3, consists of three exons and is predicted to positively regulate the expression of specific genes. LINC00518 has emerged as a key oncogenic lncRNA in multiple cancer types. It exerts its tumor-promoting effects by modulating the expression of several target genes, primarily through acting as a sponge for microRNAs (miRNAs). Additionally, LINC00518 influences critical signaling pathways, including the Wnt/β-catenin, JAK/STAT, and integrin β3/FAK pathways. Elevated levels of LINC00518 in tumor tissues are associated with increased tumor size, advanced clinical stage, metastasis, and poor survival prognosis. This review provides a comprehensive summary of the genetic characteristics, expression patterns, biological functions, and underlying mechanisms of LINC00518 in human diseases.